1983
DOI: 10.1017/s0021932000014681
|View full text |Cite
|
Sign up to set email alerts
|

Infant and child mortality in Kuwait

Abstract: SummaryThis paper examines the levels, trends and Kuwaiti–non-Kuwaiti differentials in stillbirth, infant and child mortality rates during the 1957–79 period. The present infant mortality rate (33 per 1000) and its component parts are high in contrast to those in more developed countries. But during the last few decades, the rates showed definite decline. The decline in infant and child mortality was rapid between 1955 and 1970 when the infant death rate was about 100 or more per thousand livebirths, but slowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…One of the key explanations may be the improvement of health care in Kuwaiti society, especially the reproductive health care of women and the health care of children. As reported by Kohli and Al-Omaim (1983), there has been a definite decline in child mortality since the 1970s. During this period of economic growth, health care has improved, and Kuwait is considered to be one of the top countries in the world with regard to child health care.…”
Section: Resultsmentioning
confidence: 90%
“…One of the key explanations may be the improvement of health care in Kuwaiti society, especially the reproductive health care of women and the health care of children. As reported by Kohli and Al-Omaim (1983), there has been a definite decline in child mortality since the 1970s. During this period of economic growth, health care has improved, and Kuwait is considered to be one of the top countries in the world with regard to child health care.…”
Section: Resultsmentioning
confidence: 90%
“…The ARI control program may have contributed to this decline in IMR in Bohol and may partly account for the low CFR in our hospital surveillance. The low CFR may also be partly attributed to socio‐economic progress and improvements in the standards of living (Kohli & Al‐Omaim 1983).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of SES differences that might exist despite the overall decline, only a few studies exist. Based on 1975 Census data, Kohli and Al-Omaim [15] reported that a consistent inverse association existed between the proportion of dead children and education level of the mother. Shah and Shah [12] reported on the basis of a national survey conducted in 1984-1985 that the average number of stillbirths was inversely associated with the monthly income of the household.…”
Section: Introductionmentioning
confidence: 99%